Concept and essence of the values of innovation processes (Journal of actual problems of jurisprudence, 2018)
In this article the author based on a comprehensive analysis of the concept and spirit of innovation especially considering their origin and interpretation. However, the author made an attempt to give a definition of innovation by analyzing the existing points of view expressed by the scientists on this issue.Key words: innovation, innovation, innovation characteristics , classification of innovations.